Characteristics of self-care interventions for patients with a chronic condition: A scoping review. (April 2021) - Riegel, Barbara; Westland, Heleen; Iovino, Paolo; Barelds, Ingrid; Bruins Slot, Joyce; Stawnychy, Michael A.; Osokpo, Onome; Tarbi, Elise; Trappenburg, Jaap C.A.; Vellone, Ercole; Strömberg, Anna; Jaarsma, Tiny
Abstract: Background: Self-care is a fundamental element of treatment for patients with a chronic condition and a major focus of many interventions. A large body of research exists describing different types of self-care interventions, but these studies have never been compared across conditions. Examination of heterogeneous interventions could provide insights into effective approaches that should be used in diverse patient populations. Objectives: To provide a comprehensive and standardized cross-condition overview of interventions to enhance self-care in patients with a chronic condition. Specific aims were to: 1) identify what self-care concepts and behaviors are evaluated in self-care interventions; 2) classify and quantify heterogeneity in mode and type of delivery; 3) quantify the behavior change techniques used to enhance self-care behavior; and 4) assess the dose of self-care interventions delivered. Design: Scoping review Data sources: Four electronic databases – PubMed, EMBASE, PsychINFO and CINAHL – were searched from January 2008 through January 2019. Eligibility criteria for study selection: Randomized controlled trials (RCTs) with concealed allocation to the intervention were included if they compared a behavioral or educational self- care intervention to usual care or another self-care intervention and were conducted in adults. Nine common chronic conditions were included: hypertension, coronary artery disease, arthritis, chronic kidney disease, heart failure, stroke, asthma, chronic obstructive lung disease, and type 2 diabetes mellitus. Diagnoses that are psychiatric (e.g. schizophrenia), acute rather than chronic, or benefitting little from self-care (e.g. dementia) were excluded. Studies had to be reported in English with full-text available. Results: 9309 citations were considered and 233 studies were included in the final review. Most studies addressed type 2 diabetes mellitus ( n = 85; 36%), hypertension ( n = 32; 14%) or heart failure ( n = 27; 12%). The majority (97%) focused on healthy behaviors like physical activity (70%), dietary intake (59%), and medication management (52%). Major deficits found in self-care interventions included a lack of attention to the psychological consequences of chronic illness, technology and behavior change techniques were rarely used, few studies focused on helping patients manage signs and symptoms, and the interventions were rarely innovative. Research reporting was generally poor. Conclusions: Major gaps in targeted areas of self-care were identified. Opportunities exist to improve the quality and reporting of future self-care intervention research. Registration: The study was registered in the PROSPERO database (#123, 719).